2021
DOI: 10.3390/polym13213787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Egg-Coating Material Properties by Blending Cassava Starch with Methyl Celluloses and Waxes on Egg Quality

Abstract: An egg-coating material was developed to extend the shelf-life and freshness of eggs by blending cassava starch (CS) with gelling agents and waxes. The effects of the properties of this egg coating on egg quality were investigated. Hydroxypropyl methylcellulose (HPMC), carboxymethyl cellulose (CMC), beeswax, and paraffin wax were used. CS blended with low-molecular-weight paraffin (Paraffin(L)) and CMC coating material displayed a tensile strength of 4 MPa, 34% elongation at break, 0.0039 g day−1 m−2 water vap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…The CH/PVA blended coating delayed egg weight loss by sealing eggshell pores with the highly water-resistant coating material, which decreased the evaporation rate of the internal content of the eggs. The prevention of egg weight loss using highly water-resistant coating materials has also been previously reported byRachtanapun et al (2021). In concurrence with our findings, results in research ofBahrami et al (2003) and El-Hefian et al (2011) indicated that blended films have higher tensile strength than pure CH and PVA films.…”
supporting
confidence: 93%
“…The CH/PVA blended coating delayed egg weight loss by sealing eggshell pores with the highly water-resistant coating material, which decreased the evaporation rate of the internal content of the eggs. The prevention of egg weight loss using highly water-resistant coating materials has also been previously reported byRachtanapun et al (2021). In concurrence with our findings, results in research ofBahrami et al (2003) and El-Hefian et al (2011) indicated that blended films have higher tensile strength than pure CH and PVA films.…”
supporting
confidence: 93%
“…A study conducted by Eyng et al [21], which also used carnauba wax as a coating for chicken eggs at different concentrations (12% and 15%) and temperatures (10ºC and 25ºC), demonstrated that during the storage period of the study, the weight loss in eggs coated with wax, at both concentrations and temperatures, was lower compared to the uncoated group. This indicates that regardless of temperature and concentration, the waxy coating on eggshells can preserve the internal quality of the eggs.…”
Section: Effects Of Coating and Storing Eggs With Carnauba Wax On Var...mentioning
confidence: 96%
“…When the ratio of NS and CMC was 5:5, the physical properties of the composite membrane were the best. The addition of CMC to cassava starch enhances the hydrophobicity and mechanical properties of the coating, contributing to the preservation of egg quality [69].…”
Section: Properties Of Cmcmentioning
confidence: 99%